2014
DOI: 10.1128/aac.02819-13
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Inhibition of Vibrio cholerae VipA-VipB Interaction Identifies Small-Molecule Compounds Active against Type VI Secretion

Abstract: bThe type VI secretion system (T6SS) is the most prevalent bacterial secretion system and an important virulence mechanism utilized by Gram-negative bacteria, either to target eukaryotic cells or to combat other microbes. The components show much variability, but some appear essential for the function, and two homologues, denoted VipA and VipB in Vibrio cholerae, have been identified in all T6SSs described so far. Secretion is dependent on binding of an ␣-helical region of VipA to VipB, and in the absence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Similarly, the T6SS of Acinetobacter baumannii causes a host viability decrease in Galleria mellonella ( 23 ), while Salmonella enterica serovar Typhimurium, Shigella sonnei , and Vibrio cholerae employ the T6SS to disrupt the intestinal microbiota and colonize the host gastrointestinal tract ( 24 27 ). Although the T6SS is undoubtedly involved in pathogenesis initiation, strategies targeting this virulence factor are crucially lacking ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the T6SS of Acinetobacter baumannii causes a host viability decrease in Galleria mellonella ( 23 ), while Salmonella enterica serovar Typhimurium, Shigella sonnei , and Vibrio cholerae employ the T6SS to disrupt the intestinal microbiota and colonize the host gastrointestinal tract ( 24 27 ). Although the T6SS is undoubtedly involved in pathogenesis initiation, strategies targeting this virulence factor are crucially lacking ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…A tyrosine kinase inhibitor (TKI) is a pharmaceutical drug that inhibits those TK. Recently, large numbers of small molecules of TKI have been developed for chemotherapy of cancers [ 14 , 15 ] and expanded their efficacy for treatment of infectious diseases [ 16 , 17 ]. After a preliminary screening study, we choose 3 target TKI drugs, including Erlotinib hydrochloride, Afatinib, and Sunitinib.…”
Section: Introductionmentioning
confidence: 99%
“…3D). A recent report suggests that other small molecules can interfere with T6SS function (38), but, to our knowledge, thiourea represents the first molecule identified that blocks transcription of T6SS genes. Thus, thiourea and its derivatives might be promising antibacterial drugs if they block expression of T6SS genes in organisms that rely on T6SS activity for their full virulence.…”
Section: Significancementioning
confidence: 99%